Naturalistic Study On Communication Strategy Used By Second Semester Students In Speaking Class Of English Education Department Of Muhammadiyah University Of Surakarta - Anggrantasari, Dini Inge, Endang Fauziati, M.Hum, Mauly Halwat Hikmat, Ph.D (2016)
This research aims at describing the communication strategies used by the second semester students in Speaking class of Muhammadiyah University of Surakarta. The study is also as a reference for the better problem-management in teaching-learning process. The data contain communication strategies used by the second semester students in Speaking class of English Education Department of Muhammadiyah University of Surakarta in 2015/2016 academic year. There are three sources of data in this research, namely: event, informant, and document. The writer takes 2 classes of Speaking, with the total 38 students as the subject of the research. The writer uses qualitative method in analyzing the data. The data are based on Celce-Murcia's taxonomy of communication strategies. The result of this study shows that there are five types with fourteen subtypes of communication strategies, the most dominant types of communication strategies used by second semester students in Speaking class is fillers 31,05%, and the rarely type of communication strategies used by students are topic avoidance, word coinage, literal translation, self-initiated repair 0,53%. The result above implies that teaching communication strategies are needed for students who still have limited knowledge in the target language. To maintain student's communication, communication strategies as an object in Speaking class make the students aware when they communicate with the others. Keywords: communication strategies, speaking.